Exploring Drawing Skills and Mental Images of Secondary Students on Human Digestive System through Hand Drawing - Mohapatra, Animesh Kumar; Roy, Anirban (JOURNAL OF INDIAN EDUCATION, 2018)
In consideration of the potential of drawing as an assessment and learning tool, we explored how the secondary students used it to communicate their understanding of the human digestive system—a chapter in Class X. Six schools in Bhubaneswar—three affiliated to the CBSE, two to the Odisha State Board and one to the West Bengal State Board, were randomly selected. 478 students of Class X of these schools were used for the study. They were asked to draw and label the human digestive system and respond to a close-ended questionnaire. The results revealed that the drawing skills of majority of students were poor and not monitored by the teacher for assessing the understanding level of students on the human digestive system. Several misconceptions are prevailing in the mind of the students, related to the position, shape, size and colour of various digestive organs.